About the influence of health care financing, medical personnel’s qualification and staffing to provide medical care for a patients with a cerebral stroke in Ukraine - Mishchenko, Maryna Mykhailovna; Shevchenko, Alexander Sergeevich; Mishchenko, Alexander Nykolaevich (ISGT Publishing House, 2020)
Survival of patients with cerebral stroke, both in the acute period (the “therapeutic window” after a stroke is 4.5 hours) and in the long-term (half a year after a stroke), depends on the quality of diagnosis and medical care. Ukraine is one of the countries with a high mortality rate for stroke patients, therefore, measures to improve medical care are relevant: reducing the shortage and qualifications of the neurological service staff, providing medical institutions with diagnostic equipment and medicines, creating more stroke centers, increasing state funding for treating patients.

Выживаемость больных с церебральным инсультом, как в остром периоде («терапевтическое окно» после инсульта составляет 4,5 часа), так и в отдаленном (пол года после инсульта), напрямую зависит от качества диагностики и оказания медицинской помощи. Украина входит в число стран с высокой смертностью больных инсультами, поэтому актуальны меры по улучшению медицинской помощи: уменьшения дефицита и квалификации кадров неврологической службы, обеспеченность медицинских учреждений диагностическим оборудованием и медикаментами, создания большего количества инсультных центров, увеличение государственного финансирования лечения больных.
О влиянии финансирования здравоохранения, квалификации медицинского персонала и обеспеченности медицинскими кадрами на оказание медицинской помощи больным с мозговым инсультом в Украине
Keywords: cardiovascular diseases; cerebral stroke; survival; medical staffing; epidemiology; health care costs; stroke centers; сердечно-сосудистые заболевания; церебральный инсульт; выживаемость; обеспеченность медицинскими кадрами; эпидемиология; расходы на здравоохранение; инсультные центры